2010
DOI: 10.1098/rspb.2010.2306
|View full text |Cite
|
Sign up to set email alerts
|

Eye-gaze and arrow cues influence elementary sound perception

Abstract: We report a novel effect in which the visual perception of eye-gaze and arrow cues change the way we perceive sound. In our experiments, subjects first saw an arrow or gazing face, and then heard a brief sound originating from one of six locations. Perceived sound origins were shifted in the direction indicated by the arrows or eye-gaze. This perceptual shift was equivalent for both arrows and gazing faces and was unaffected by facial expression, consistent with a generic, supramodal attentional influence by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
(72 reference statements)
3
6
1
Order By: Relevance
“…Recent findings have demonstrated that emotion modulates some basic aspects of perception, such as visual contrast sensitivity [6], but not others, such as auditory directional attention [7]. The selectivity of emotional effects on perception is consistent with anecdotal reports that specific phobias may induce categoryspecific distortions of perception [8].…”
Section: Correspondencessupporting
confidence: 78%
“…Recent findings have demonstrated that emotion modulates some basic aspects of perception, such as visual contrast sensitivity [6], but not others, such as auditory directional attention [7]. The selectivity of emotional effects on perception is consistent with anecdotal reports that specific phobias may induce categoryspecific distortions of perception [8].…”
Section: Correspondencessupporting
confidence: 78%
“…Recent findings have demonstrated that emotion modulates some basic aspects of perception, such as visual contrast sensitivity [6], but not others, such as auditory directional 5 attention [7]. The selectivity of emotional effects on perception is consistent with anecdotal reports that specific phobias may induce category-specific distortions of perception [8].…”
supporting
confidence: 59%
“…We constantly need to use joint and shared attention with others by recognizing cues and targets that belong to different modalities; therefore, it is important to investigate the effect of joint attention under cross-modal conditions. Previous studies have examined joint attention in typically developing individuals under cross-modal conditions (Borjon, Shepherd, Todorov, & Ghazanfar, 2010;Newport & Howarth, 2009). Both studies presented visual cues and auditory targets and showed significant gaze-triggered joint attention under cross-modal conditions, as in a uni-modal paradigm.…”
mentioning
confidence: 98%